Kv1 channels and neural processing in vestibular calyx afferents - Meredith, Frances L.; Kirk, Matthew E.; Rennie, Katherine J. (Frontiers in Systems Neuroscience, 2015)
Potassium-selective ion channels are important for accurate transmission of signals from auditory and vestibular sensory end organs to their targets in the central nervous system. During different gravity conditions, astronauts experience altered input signals from the peripheral vestibular system resulting in sensorimotor dysfunction. Adaptation to altered sensory input occurs, but it is not explicitly known whether this involves synaptic modifications within the vestibular epithelia. Future investigations of such potential plasticity require a better understanding of the electrophysiological mechanisms underlying the known heterogeneity of afferent discharge under normal conditions. This study advances this understanding by examining the role of the Kv1 potassium channel family in mediating action potentials in specialized vestibular afferent calyx endings in the gerbil crista and utricle. Pharmacological agents selective for different sub-types of Kv1 channels were tested on membrane responses in whole cell recordings in the crista. Kv1 channels sensitive to α-dendrotoxin and dendrotoxin-K were found to prevail in the central regions, whereas K+ channels sensitive to margatoxin, which blocks Kv1.3 and 1.6 channels, were more prominent in peripheral regions. Margatoxin-sensitive currents showed voltage-dependent inactivation. Dendrotoxin-sensitive currents showed no inactivation and dampened excitability in calyces in central neuroepithelial regions. The differential distribution of Kv1 potassium channels in vestibular afferents supports their importance in accurately relaying gravitational and head movement signals through specialized lines to the central nervous system. Pharmacological modulation of specific groups of K+ channels could help alleviate vestibular dysfunction on earth and in space.